2020
DOI: 10.1021/acs.energyfuels.0c01812
|View full text |Cite
|
Sign up to set email alerts
|

Impact of n-Hexanol Blending on Morphology, Nanostructure, Graphitization, and Oxidation Characteristics of Diesel Particles

Abstract: As a promising alternative fuel with favorable properties and attractive prospects, the application of n-hexanol in diesel engines has aroused the interest of researchers. This study investigated the effects of mixing with n-hexanol on the morphology, nanostructure, graphitization, and oxidation reactivity of soot particles generated from a diesel engine. Experiments were performed on a turbocharged, four-cylinder direct-injection diesel engine fueled with D100 (neat diesel fuel), DH15 (15% nhexanol and 85% di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The sintering process of silver powder can be roughly divided into two processes: the removal of organic matter and the densification of silver powder. In the removal stage of organic matter, the primary component of the organic carrier, n -hexanol, is rapidly removed at 157 °C . The removal temperature of the surface-modified organic matter of the wrinkled silver powder and the smooth silver powder is around 230 °C (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sintering process of silver powder can be roughly divided into two processes: the removal of organic matter and the densification of silver powder. In the removal stage of organic matter, the primary component of the organic carrier, n -hexanol, is rapidly removed at 157 °C . The removal temperature of the surface-modified organic matter of the wrinkled silver powder and the smooth silver powder is around 230 °C (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…In the removal stage of organic matter, the primary component of the organic carrier, n-hexanol, is rapidly removed at 157 °C. 36 The removal temperature of the surface-modified organic matter of the wrinkled silver powder and the smooth silver powder is around 230 °C (Figure 8a,b). Therefore, the organic carrier is preferentially removed, and it is the surfactant remaining on the surface of the silver powder that determines the start of sintering.…”
Section: Aggregation and Growth Of Wrinkled Silver Powdermentioning
confidence: 99%
“…Relatively more reactive soot would result in slower accumulation inside the filter and also faster filter regeneration. 15,16 In an investigation related to oxygenated fuel, Wang et al 17 investigated 15% and 30% v/v blend of n-hexanol with diesel at 125 Nm engine load. With increase in hexanol ratio, authors reported relatively lower degree of graphitization.…”
Section: Introductionmentioning
confidence: 99%